The Effectiveness of Electronic Government in the Application-Based Siskeudes in Paconne Village, Luwu Regency. - Juwita Lukman; Muh. Akmal Ibrahim; Nurdin Nara (Enrichment : Journal of Management, 2021)
For the village government, the use of information technology for village-level financial management is becoming a new aspect of its duties and functions, one of which is finance. In order to support the effectiveness of e-government-based financial management through SISKEUDES, the government issued regulations in the form of Regulation No. 20 of 2018 on Rural Financial Management by the Minister of the Interior. The purpose of the siskeudes app is to achieve responsible and transparent village governance. This study uses qualitative and descriptive methods. This research uses the theory of organizational effectiveness in the application of organizational e-government by examining three indicators, namely structure, process and results. The results show that there are still differences in the application of e-government, so e-government fails to operate effectively.